2012
DOI: 10.4137/grsb.s10224
|View full text |Cite
|
Sign up to set email alerts
|

A Next-Generation Sequencing Approach to Study the Transcriptomic Changes during the Differentiation of Physarum at the Single-Cell Level

Abstract: Physarum polycephalum is a unicellular eukaryote belonging to the amoebozoa group of organisms. The complex life cycle involves various cell types that differ in morphology, function, and biochemical composition. Sporulation, one step in the life cycle, is a stimulus-controlled differentiation response of macroscopic plasmodial cells that develop into fruiting bodies. Well-established Mendelian genetics and the occurrence of macroscopic cells with a naturally synchronous population of nuclei as source of homog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The cellular commitment to sporulation is associated to the differential expression of developmentally regulated genes [ 13 ]. Based on transcriptome data [ 13 , 14 ] we have previously designed gene specific primers for the quantification of the transcripts of a set of 35 genes with a single GeXP RT-PCR reaction. The concentrations of the gene-specific reverse primers were attenuated (adjusted) so that amplification of each of the 35 cDNAs yields a sufficient amount of each fragment to be resolved side-by-side during electrophoretic separation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cellular commitment to sporulation is associated to the differential expression of developmentally regulated genes [ 13 ]. Based on transcriptome data [ 13 , 14 ] we have previously designed gene specific primers for the quantification of the transcripts of a set of 35 genes with a single GeXP RT-PCR reaction. The concentrations of the gene-specific reverse primers were attenuated (adjusted) so that amplification of each of the 35 cDNAs yields a sufficient amount of each fragment to be resolved side-by-side during electrophoretic separation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Reannotation of the P. polycephalum genome We downloaded the Physarum polycephalum genome assembly and annotation from https://www.regulationsbiologie.ovgu.de/ Downloads/Physarum+polycephalum+Genome+Resource.html, and RNA-seq from NCBI's SRA database (accession numbers DRR047256, ERR089824-ERR089827, and ERR557103-ERR557120). 16,17,45,46 To reannotate the genome, we combined several de novo and reference-based approaches. First, we generated a de novo transcriptome from the aggregate RNA-seq data using Trinity 47 (v2.5.1).…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…Sporulation is associated with a cascade of differentially expressed genes [19][20][21][22]. By repeatedly taking samples at different time points after triggering sporulation with a far-red light pulse, we have shown that individual plasmodial cells proceed to sporulation along variable pathways that involve qualitatively different correlation patterns of differentially expressed genes [23].…”
Section: Introductionmentioning
confidence: 95%